Use of platelet-rich plasma (PRP) and injectable platelet-rich fibrin (i-PRF) in oral lichen planus treatment: a systematic review of randomized controlled trials - Wojciech Niemczyk; Katarzyna Janik; Stanisław Niemczyk; Jacek Żurek; Edward Lynch; Steven Parker; Mark Cronshaw; Dariusz Skaba; Rafał Wiench (BMC Oral Health)
Abstract Background Lichen planus (LP) is a chronic inflammatory disease that affects the skin and mucous membranes, including the oral cavity. The prevalence of oral lichen planus (OLP) in the general population is estimated to be between 0.5% and 2%, with a higher incidence observed in women aged between 30 and 80 years. The etiology of OLP remains unclear, which presents a significant challenge in terms of diagnosis and treatment. This systematic review assessed the efficacy of platelet-rich plasma (PRP) and injectable platelet-rich fibrin (i-PRF) in the treatment of OLP. Methods A comprehensive literature search was conducted via multiple databases in accordance with the PRISMA 2020 guidelines. Results A total of seven randomized controlled trials were subjected to analysis. It has been demonstrated that both PRP and i-PRF have the capacity to significantly improve clinical outcomes, including pain and lesion severity. However, the majority of studies have not demonstrated statistically significant differences between PRP/i-PRF and corticosteroid treatments. Conclusions While PRP and i-PRF demonstrate potential in alleviating symptoms and promoting tissue healing, their effectiveness appears to be analogous to that of corticosteroids in the majority of RCTs. Further high-quality, standardized studies are required to substantiate their function as alternative or adjunctive therapies in the management of OLP. Trial registration This systematic review was registered in the International Prospective Register of Systematic Reviews (PROSPERO) on 28 November 2024 (PROSPERO 2024 CRD42024615291).